2016
DOI: 10.1159/000442574
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Familial Susceptibility to MPTP in a Common Marmoset Model for Parkinson's Disease

Abstract: Introduction: Insight into susceptibility mechanisms underlying Parkinson's disease (PD) would aid the understanding of disease etiology, enable target finding and benefit the development of more refined disease-modifying strategies. Methods: We used intermittent low-dose MPTP (0.5 mg/kg/week) injections in marmosets and measured multiple behavioral and neurochemical parameters. Genetically diverse monkeys from different breeding families were selected to investigate inter- and intrafamily differences in susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…We provide values for baseline hair cortisol concentrations for common marmosets and tufted capuchin monkeys. The results for marmosets are similar to those reported by Franke et al (), who followed the same assay protocol. As seen in Table , other studies have obtained notably different hair cortisol values in common marmosets.…”
Section: Discussionsupporting
confidence: 89%
“…We provide values for baseline hair cortisol concentrations for common marmosets and tufted capuchin monkeys. The results for marmosets are similar to those reported by Franke et al (), who followed the same assay protocol. As seen in Table , other studies have obtained notably different hair cortisol values in common marmosets.…”
Section: Discussionsupporting
confidence: 89%
“…Two different cell sources for auto-and allografts (adrenal medullary tissue and ventral mesencephalic region of fetuses respectively) paved the way for brain repair through cell transplantation. Adrenal medulla grafts which contained chromaffin cells that synthesized DA were grafted in 6-OHDA rats as an alternative source of catecholamineproducing cells (Freed et al, 1981;Stromberg et al, 1985) with the benefit of avoiding ethical and immunological issues linked to the graft of fetal tissue. Even if testing in the 6-OHDA NHP model returned minimal survival of transplanted adrenal medullary tissue (Morihisa et al, 1984), it was rapidly followed by first clinical trials in the few patients reporting clinical improvement (Lindvall et al, 1987;Madrazo et al, 1987).…”
Section: The Grafted Cells: Types and Characteristicsmentioning
confidence: 99%
“…At the time, testing of fVM striatal grafts on the recently developed NHP MPTP model (Burns et al, 1983) returned satisfactory results, with behavioral recovery in monkeys exhibiting mild to severe parkinsonism (Redmond Jr. et al, 1986;Annett et al, 1990Annett et al, , 1994Annett et al, , 1995Taylor et al, 1991;Starr et al, 1999;Collier et al, 2002), confirming trials in the rodent model of PD. First clinical trials (Lindvall et al, 1988) were again initially promising (Lindvall et al, 1990) but were later held back due to efficiency concerns following studies with a larger number of patients and randomized, double-blind, placebo-controlled protocols (Freed et al, 2001;Olanow et al, 2003) that showed no significant difference between grafted patients and placebo, with several patients developing graft-induced dyskinesia. Nevertheless, retrospective analyses and reports on those clinical trials of fVM striatal grafts demonstrated their efficiency either clinically (Kefalopoulou et al, 2014), histologically (Li et al, 2016), behaviorally (Gordon et al, 2004) or functionally (Politis and Piccini, 2010).…”
Section: Fetal Ventral Mesencephalonmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to rodents, marmosets are lissencephalic, a feature that confers the advantage of making sensorimotor, visual, and auditory cortical areas easily mapped by neuroimaging techniques and accessible to electrophysiology. Similar to humans, the brain of marmosets have a large amount of white matter, a feature that may confer them significant advantages as a translational model of brain disease, including multiple sclerosis (Uccelli et al, ; Boretius et al, ; t Hart et al, ; Helms et al, ; Gaitan et al, ; Maggi et al, ; Kap et al, ), stroke (Marshall et al, ; Virley et al, ; Bihel et al, ; Teo and Bourne, ; Puentes et al, ), Parkinson's disease (Hikishima et al, ; Yun et al, ; Franke et al, ) and Alzheimer's disease (Maclean et al, ). Recently, transgenic marmoset lines with germline transmission have been demonstrated (Sasaki et al, ), opening up novel approaches to understanding neuronal circuitry and function in the primate brain, and to make significant advancements in the study of neurological and neuropsychiatric disorders (Okano et al, ; Izpisua Belmonte et al, ; Huang et al, ).…”
Section: Introductionmentioning
confidence: 99%